Effects of platelet-rich plasma on liver regeneration in CCl4-induced hepatotoxicity model. (16th November 2016) - Mafi, Afsaneh; Dehghani, Farzaneh; Moghadam, Abbas; Noorafshan, Ali; Vojdani, Zahra; Talaei-Khozani, Tahereh
Abstract: Numerous bioactive growth factors and cytokines in platelet-rich plasma (PRP) have recently made it an attractive biomaterial for therapeutic purposes. These growth factors have the potential to regenerate the injured tissues. The aim of this study was to investigate the therapeutic effects of PRP in hepatotoxic animal model. Hepatotoxicity was induced in rats by oral administration of 4 mL/kg/week of CCl4 diluted 1:1 in corn oil for 10 weeks. To confirm the hepatotoxicity, 24 h after the last CCl4 administration, blood samples were collected via cardiac puncture to assess the serum levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, albumin, total protein, and total bilirubin. Twenty-four hours after blood collection, the experimental animals received a single injection of PRP (1 mL) via the anterior mesenteric vein. One week later, all biochemical tests were performed again, and the rats were scarified and their livers were removed, prepared histologically, and stained. The stereological analyses were performed to evaluate the effects of PRP on histopathological features of CCl4 -treated livers. The results were compared statistically with the corresponding control and CCl4 +normal saline (NS)-treated animals. A significant decrease in the number and volume of hepatocytes ( p = 0.01), and also a reduction in the volume of sinusoids ( p = 0.001) and connective tissue ( p = 0.04), were observed in the PRP-treated animals compared with the CCl4 +NS-treated ones. Our findings demonstrated that application of PRP had beneficial effects on CCl4 -induced fibrosis; however, it had detrimental effects on the total number of hepatocytes and the volume of hepatocytes and sinusoidal spaces.